Review of Ge(GeSn) and InGaAs Avalanche Diodes Operating in the SWIR Spectral Region - Yuanhao Miao; Hongxiao Lin; Ben Li; Tianyu Dong; Chuangqi He; Junhao Du; Xuewei Zhao; Ziwei Zhou; Jiale Su; He Wang; Yan Dong; Bin Lu; et al. (Nanomaterials, 2023)
Among photodetectors, avalanche photodiodes (APDs) have an important place due to their excellent sensitivity to light. APDs transform photons into electrons and then multiply the electrons, leading to an amplified photocurrent. APDs are promising for faint light detection owing to this outstanding advantage, which will boost LiDAR applications. Although Si APDs have already been commercialized, their spectral region is very limited in many applications. Therefore, it is urgently demanded that the spectral region APDs be extended to the short-wavelength infrared (SWIR) region, which means better atmospheric transmission, a lower solar radiation background, a higher laser eye safety threshold, etc. Up until now, both Ge (GeSn) and InGaAs were employed as the SWIR absorbers. The aim of this review article is to provide a full understanding of Ge(GeSn) and InGaAs for PDs, with a focus on APD operation in the SWIR spectral region, which can be integrated onto the Si platform and is potentially compatible with CMOS technology.